2017
DOI: 10.1210/js.2017-00433
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Cardiac GHSR1a-Ghrelin System Correlate With Myocardial Dysfunction in Diabetic Cardiomyopathy in Mice

Abstract: Ghrelin and its receptor, the growth hormone secretagogue receptor 1a (GHSR1a), are present in cardiac tissue. Activation of GHSR1a by ghrelin promotes cardiomyocyte contractility and survival, and changes in myocardial GHSR1a and circulating ghrelin track with end-stage heart failure, leading to the hypothesis that GHSR1a is a biomarker for heart failure. We hypothesized that GHSR1a could also be a biomarker for diabetic cardiomyopathy (DCM). We used two models of streptozotocin (STZ)-induced DCM: group 1, ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 38 publications
3
30
0
Order By: Relevance
“…Serial echocardiographic assessment of LV function following cardiac transplant 5 showed LV recovery to an LVEF > 50% in 80% of patients by 1 month PTx. By 6 months PTx, 6 all patients had normal LV function ( Table 2). Although most patients were receiving HF 7 medications, i.e., angiotensin converting enzyme (ACE) inhibitors/beta blockers/diuretics, prior to 8 transplantation, only a small number continued to receive these medications following surgery.…”
Section: Cardiac Transplant Patient Cohortmentioning
confidence: 95%
See 3 more Smart Citations
“…Serial echocardiographic assessment of LV function following cardiac transplant 5 showed LV recovery to an LVEF > 50% in 80% of patients by 1 month PTx. By 6 months PTx, 6 all patients had normal LV function ( Table 2). Although most patients were receiving HF 7 medications, i.e., angiotensin converting enzyme (ACE) inhibitors/beta blockers/diuretics, prior to 8 transplantation, only a small number continued to receive these medications following surgery.…”
Section: Cardiac Transplant Patient Cohortmentioning
confidence: 95%
“…By 6 months PTx, 6 all patients had normal LV function ( Table 2). Although most patients were receiving HF 7 medications, i.e., angiotensin converting enzyme (ACE) inhibitors/beta blockers/diuretics, prior to 8 transplantation, only a small number continued to receive these medications following surgery.…”
Section: Cardiac Transplant Patient Cohortmentioning
confidence: 95%
See 2 more Smart Citations
“…Ghrelin actions are mediated via activation of the G protein coupled receptor (GPCR) growth hormone secretagogue receptor type 1a (GHS‐R1a) . It was originally reported that GHS‐R1a was found within the pituitary gland and hypothalamus, but recent work has revealed a more widespread expression in other tissues, including the brain and heart . GHS‐R1a is also reported to be differentially expressed in certain cancer cells.…”
Section: Figurementioning
confidence: 99%